A Very Low Band Gap Diketopyrrolopyrrole–Porphyrin Conjugated Polymer. Issue 4 (17th March 2017) - Bucher, Léo; Tanguy, Loïc; Fortin, Daniel; Desbois, Nicolas; Harvey, Pierre D.; Sharma, Ganesh D.; Gros, Claude P.
Abstract: A porphyrin–diketopyrrolopyrrole‐containing polymer (poly(porphyrin– diketopyrrolopyrrole) (PPDPP )) shows impressive molar absorption coefficients from λ =300 to 1000 nm. The photophysical and structural properties ofPPDPP have been studied. WithPPDPP as the electron donor and [6, 6]‐phenyl C71 butyric acid methyl ester (PC71 BM) as the electron acceptor, the bulk heterojunction polymer solar cell showed overall power conversion efficiencies of 4.18 and 6.44 % for as‐cast and two‐step annealing processedPPDPP :PC71 BM (1:2) active layers, respectively. These results are quite impressive for porphyrin‐containing polymers, especially when directly included in the π‐conjugated backbone, and offer interesting perspectives for the design of new materials based on this chromophore. Abstract : Improved absorption : A porphyrin–diketopyrrolopyrrole‐containing polymer shows impressive molar absorption coefficients from λ =300 to 1000 nm. The photophysical and structural properties of this polymer, along with application in a bulk heterojunction polymer solar cell, are discussed (see figure).